Growing-season soil microbial respiration response to long-term no tillage and spring ridge tillage - Wang, Gang; Jia, Honglei; Zhuang, Jian; Glatzel, Stephan; Bennett, John McL.; Zhu, Yingcan (International Journal of Agricultural and Biological Engineering, 2020)
No tillage (NT) and spring ridge tillage (SRT) are two common applications of conservation tillage. Although conservation tillage is known to exert major control over soil microbial respiration (SMR), the growing-season SMR response to these two applications remains elusive. In order to better understand the influence of conservation tillage practices, this experiment was conducted in an experimental field using NT and SRT for 17 years. In situ measurements of SMR, soil temperature and soil water content (SWC) were performed. Soil samples were collected to analyze soil porosity, soil microbial biomass (SMB) and soil enzymatic activities. Results show that the two conservation tillage systems had a significant difference (p<0.05) in terms of SMR; the SMR of NT was 14.7 mg∙C/m2∙h higher than that of SRT. In terms of soil temperature and soil enzymatic activities, the two treatments were not significantly different (p>0.05). Despite SRT increasing the proportion of micro-porosities and meso-porosities, the soil macro-porosities for NT were 7.37% higher than that of SRT, which resulted in higher bacteria and fungi in NT. Owing to SRT damaged the hypha, which had disadvantage in soil microbe protection. Inversely, less soil disturbance was a unique advantage in NT, which was in favor of improving soil macro-pores and SWC. Redundancy analyses (RDA) showed SMR was positively correlated with soil macro-pores, SMB and SWC. Furthermore, the Pearson correlation test indicated that SMB and soil enzymatic activities did not have a significant correlation (p>0.05). This study results suggest that SRT is more conducive to carbon sequestration compared with NT in cropland. Keywords: no tillage, spring ridge tillage, soil microbial respiration, microbial biomass, soil porosity, soil enzymatic activity DOI: 10.25165/j.ijabe.20201304.5587 Citation: Wang G, Jia H L, Zhuang J, Glatzel S, Bennett J M, Zhu Y C. Growing-season soil microbial respiration response to long-term no tillage and spring ridge tillage. Int J Agric & Biol Eng, 2020; 13(4): 143–150.